PROHIBITING DIVORCE, PRESERVING HARMONY : A MAQĀṢIDI AND GENDER JUSTICE ANALYSIS OF THE MAK DIJUK SIANG TRADITION IN LAMPUNG PEPADUN COMMUNITY, INDONESIA - Hanifah Nur Qotrunnada; Qosim Khoiri Anwar (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to explain the practice of the Mak Dijuk Siang tradition as a prohibition of divorce in the indigenous people of Lampung Pepadun Ratu Buay Semenguk and assess its relevance through the perspective of maqāṣid al-syarī'ah and gender justice theory. This tradition places marriage as a social institution that must be maintained through multi-layered conflict resolution mechanisms, ranging from the nuclear family to traditional contractors, so that divorce is seen as an act that undermines clan honor and social stability. The study used a descriptive-analytical qualitative method by combining primary data from interviews and secondary data from Islamic family law literature, maqāṣid al-syarī'ah, and gender studies. The results of the study show that Mak Dijuk Siang is in line with the principles of Islamic family law which emphasizes family reconciliation and mediation before divorce is taken. Within the framework of maqāṣid al-syarī'ah Jasser Auda, this tradition functions to comprehensively protect honor, descent, and social welfare. Gender analysis shows the potential for inequality due to patrilineal structures, but customary practices also contain protective mechanisms through the role of traditional leaders that function to maintain balance and justice. This tradition can be maintained as long as it is interpreted adaptively and remains oriented towards family justice.